2021
DOI: 10.1039/d0ra10775a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced gas separation and mechanical properties of fluorene-based thermal rearrangement copolymers

Abstract: The fluorene-based thermal rearrangement copolymers exhibited excellent gas separation and mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…The CARDO structure and the present of -C(CF 3 ) 2 -in the molecular backbone enlarged the molecular chain spacing and reduced the intermolecular forces, thus decreasing the mechanical stability of the films. In contrast to membrane materials reported in the literature, such as PCZ, 41 6FDA-NDA/DABA, 42 and TR copolymer 43 (as outlined in Table 4), the polyimide membranes in our study exhibit comparatively superior mechanical properties.…”
Section: Mechanical Propertiescontrasting
confidence: 72%
See 1 more Smart Citation
“…The CARDO structure and the present of -C(CF 3 ) 2 -in the molecular backbone enlarged the molecular chain spacing and reduced the intermolecular forces, thus decreasing the mechanical stability of the films. In contrast to membrane materials reported in the literature, such as PCZ, 41 6FDA-NDA/DABA, 42 and TR copolymer 43 (as outlined in Table 4), the polyimide membranes in our study exhibit comparatively superior mechanical properties.…”
Section: Mechanical Propertiescontrasting
confidence: 72%
“…The FFV of the 41 49.6 1.47 0.023 --6FDA-NDA/DABA (9:1) 42 58. 4 4.8 2.3 --CP-4:6-350 43 59.2 2.3 2.1 --CP-4:6-400 43 50.9 2.7 2.0 --CP-4:6-450 43 21.2 1.2 1.8 -a T S : tensile strength; T M : tensile modulus; E b : elongation at break. copolymer was investigated using molecular dynamics simulations, and the relative error was controlled within ±5% of measured and simulated densities.…”
Section: Density and Fractional Free Volumementioning
confidence: 99%
“…Taking HPPBO-400 as an example, under the same heat treatment conditions, the elongation at break and elastic modulus of HPPBO were 1.10% and 1.47 GPa, while those of Co-PBO-DAM-400 and Co-PBO-DETDA-400 are 2.61%, 21.49 GPa and 1.76%, 14.05 GPa, respectively. Therefore, the non-TR able DAM and DETDA moieties improved the roughness of the XTR polymer by increasing the values of elastic modulus and elongation at break. ,, It could be concluded that although copolymerization reduced the hydrogen bonding between polymer chains that might result in more flexible polymer chains, , copolymerization of a diamine with bulky structure could hinder the rotation ability of polymer chains so that improved stiffness of the polymer. , …”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31][32][33][34] Due to the transition from imide ring to benzoxazole structure, hydroxyl-containing polyimide (HPI) is transformed into polybenzoxazole (PBO), and a large amount of small molecule gas CO 2 is released. [35][36][37][38][39][40][41] TR polymers exhibit excellent gas permeability and moderate selectivity because of unique "hourglass" micropore structure, which have become a new generation of gas separation membrane materials. 42 The gas separation process of TR polymer is mainly followed by the solution-diffusion mechanism, accompanied by the sieving mechanism due to the existence of pore structures.…”
Section: Introductionmentioning
confidence: 99%
“…42 The gas separation process of TR polymer is mainly followed by the solution-diffusion mechanism, accompanied by the sieving mechanism due to the existence of pore structures. According to the literatures, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] the rearrangement reaction and gas separation performance of TR polymers are mostly affected by many factors, such as chemical structure, glass transition temperature (T g ), thermal treatment atmosphere, time and temperature. For example, the HPI containing exible linkage is easy to rearrange at a relatively low temperature because of better motion ability of chain segment, but the increase of gas permeability is not very signicant.…”
Section: Introductionmentioning
confidence: 99%